Política fiscal y familia / Carpio García, Maximino (coord.) ; Álvarez Rendueles, José Ramón ... [et al.] - Carpio García, MaximinoÁlvarez Rendueles, José Ramón (Economía Española; 10)
"Programa de economía familiar"